Reasons for a conflict: Social rights recognition and the classic theory of constitutional rights - González Tugas, Juan Andrés (Derecho Público Iberoamericano, 2019)
This article elaborates on the recognition of social rights and the classical theory of constitutional rights, and aims to identify the tension between them. To this end, the author identifies the possible versions of the classic constitutional rights theory, some of its features and their typology.